Associations between breastfeeding rates and infant disease: A survey of 2338 Czech children. Issue 3 (22nd April 2019) - Parizkova, Petra; Dankova, Nika; Frühauf, Pavel; Jireckova, Jitka; Zeman, Jiri; Magner, Martin
Abstract : Aim: Evidence has demonstrated that breastfeeding is the optimal nutrition for infants. The present study aims to report possible associations of the duration of full or partial breastfeeding with selected health outcomes during infancy. Methods: Data from 2304 mothers were obtained by online mother‐reported questionnaires at the age of 1 year of the child, providing information on full and partial breastfeeding durations, the frequency of infant upper respiratory tract infections and possible antibiotics use, and the occurrence of allergic diseases. Results: Overall breastfeeding initiation rates (i.e. including both partial and full breastfeeding rates counted together) were 97.8%, declined to 95.1% at the age of 3 months, and remained as high as 90.0% at 6 months. At 1 year, 74.7% of children were still partially breastfed. There was no significant benefit of either full or partial breastfeeding over formula feeding for upper respiratory tract infection rates. Fully breastfed children had a significantly lower risk of early exposure to antibiotics when compared with either partially breastfed (odds ratio, OR: 0.74; 95% CI: 0.56, 1.00, P  = 0.048) or formula‐fed (OR: 0.67; 95% CI: 0.46, 1.0, P  = 0.047) children. We found a neutral effect of breastfeeding on the development of allergies. Conclusions: Although no significant association between either full or partial breastfeeding versus formula feeding and the occurrence of respiratory infections during infancy was found, we demonstrated a significantly lower risk of early exposure to antibiotics in fully breastfed children when compared with those either partially breastfed or formula‐fed.